2021
DOI: 10.1038/s41598-021-01097-6
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil improves hippocampal brain injuries and restores neuronal development after neonatal hypoxia–ischemia in male rat pups

Abstract: The hippocampus is a fundamental structure of the brain that plays an important role in neurodevelopment and is very sensitive to hypoxia–ischemia (HI). The purpose of this study was to investigate the effects of sildenafil on neonatal hippocampal brain injuries resulting from HI, and on neuronal development in this context. HI was induced in male Long–Evans rat pups at postnatal day 10 (P10) by a left common carotid ligation followed by a 2-h exposure to 8% oxygen. Rat pups were randomized to vehicle or silde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Subsequently, PKG targets different pathways ( Figure 1 ). Sildenafil has been found to enhance neurogenesis and synaptic plasticity through the activation of the PI3K/Akt pathway in adults ( Peixoto et al, 2015 ) and neonates ( Yazdani et al, 2021 ). In a mice model of autoimmune encephalomyelitis, sildenafil inhibited microglia activation and the death of oligodendrocytes through the mitogen-activated protein kinase (MAPK) signaling pathway ( Duarte-Silva et al, 2018 , 2021 ).…”
Section: Mechanisms Of Action Of Sildenafilmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, PKG targets different pathways ( Figure 1 ). Sildenafil has been found to enhance neurogenesis and synaptic plasticity through the activation of the PI3K/Akt pathway in adults ( Peixoto et al, 2015 ) and neonates ( Yazdani et al, 2021 ). In a mice model of autoimmune encephalomyelitis, sildenafil inhibited microglia activation and the death of oligodendrocytes through the mitogen-activated protein kinase (MAPK) signaling pathway ( Duarte-Silva et al, 2018 , 2021 ).…”
Section: Mechanisms Of Action Of Sildenafilmentioning
confidence: 99%
“… Yazdani et al (2016) demonstrated that per os treatment with sildenafil—started 24 h after hypoxia-ischemia at P10 and continued twice a day for 7 consecutive days (14 doses)—could cause a significant increase in the number of neurons near the infarct boundary 20 days post-injury (Vannuci rat model at P10), with the higher doses being the most efficient (10 and 50 mg/kg). Their follow-up study demonstrated that sildenafil may be neuroprotective in the neonatal brain by preventing apoptosis, but also neurorestorative by promoting neurogenesis ( Yazdani et al, 2021 ). Engels et al (2017) found an increased number of immature neurons in the ipsilateral subventricular zone and striatum after a single intraperitoneal dose of sildenafil (10 mg/kg) given 2 h post-hypoxia-ischemia at P9.…”
Section: Effects Of Sildenafil On Neuronsmentioning
confidence: 99%
“…The Phosphatidylinositol-3-kinase (PI3K) pathway has already been identified to play an important role in cell survival of endogenous neurogenesis and many studies have focused on use of the PI3K pathway to treat brain injury after stroke ( 47 ). A recent study ( 48 ) has shown that PI3K activating its downstream effector protein kinase B (Akt) can improve hippocampal brain injuries and restore neuronal development after neonatal HIBD, which demonstrates that the activation of PI3K/Akt pathway can promote endogenous neurogenesis induced by HIBD.…”
Section: Molecular Mechanisms Involved In Endogenous Neurogenesis Aft...mentioning
confidence: 99%
“…cGMP is involved in many physiological processes as a second messenger, especially in the production of neurons [ 9 ]. The classic PDE5 inhibitor sildenafil has been used to treat erectile dysfunction (ED) and AIS [ 10 , 11 ] in clinic, but its serious side effects such as headache and increased risk of melanoma, have limited its clinical use [ 12 ]. Icariside II (ICS II) has recently been identified as a PDE5 inhibitor.…”
Section: Introductionmentioning
confidence: 99%